Madhuca indica Inhibits Breast Cancer Cell Proliferation by Modulating COX-2 Expression - Ghosh, Paramita; Mitra, Debarpan; Mitra, Sreyashi; Ray, Sudipta; Banerjee, Samir; Murmu, Nabendu (Current Molecular Medicine, 2018)
Background: Madhuca indica belongs to the family sapotaceae, commonly known as Mahua. It is primarily known for alcoholic beverage production and is reported to have anti-inflammatory, analgesic and antipyretic properties. Madhuca indica has also been reported to be effective in several diseases. Objective: This study was undertaken to check the anticancer efficacy and chemopreventive effect of methanolic extract of Mahua flower (ME) on human breast cancer cell lines MCF-7 and MDA-MB-468. Method: The cytotoxic and anti-proliferative effects on MCF-7 and MDA-MB-468 cells were studied by MTT, hexosaminidase and colony formation assay. Expression of caspase 3/7 was assessed by flow cytometry and western blot analysis. Expression of COX-2 was evaluated by western blot analysis, luciferase assay and mRNA analysis. Results: ME inhibited the proliferation of breast cancer cells by inducing apoptosis through up-regulating the expression of Caspase 3/7 (P < 0.0001). Our results showed a decrease in the expression of COX-2 mRNA and COX-2 protein in both MCF-7 and MDA-MB-468 cells with an increase in ME concentration. Furthermore synergistic effect of ME and chemotherapeutic drug paclitaxel was also studied in MCF-7 and MDA-MB- 468 cells which were found to be more effective (P < 0.0001) than treatment of either ME or paclitaxel alone. Results were analyzed by ANOVA and Pearson correlation analysis. Conclusion: All these experiments suggest that ME inhibits breast cancer cell proliferation and apoptosis by inhibiting the expression of COX-2 in MCF-7 and MDAMB- 468 cells. This work further highlighted that ME may enhance the potentiality of paclitaxel in breast cancer treatment.
Keywords: NF-ΚB